Multifocality and Detectability of Prostate Cancer with 3-Tesla Multiparametric Magnetic Resonance Imaging: Correlation with Radical Prostatectomy Mapping Histopathology - Serdar Karadağ; Deniz Noyan Özlü; Ahmet Hacıislamoğlu; Ömer Yıldız; Halil Fırat Baytekin; Mithat Ekşi; Hakan Polat; Alper Bitkin; Ali İhsan Taşçı (International Journal of Clinical Practice)
Background. We aimed to determine the multifocality and detectability of prostate cancer (Pca) with 3-Tesla (3T) multiparametric magnetic resonance imaging (mpMRI). Methods. The data of the patients who underwent radical prostatectomy in our institution between April 2020 and April 2021 were analyzed. Patients were included in the study at the stage of radical prostatectomy. Demographic and histopathological data were retrospectively collected, and then MRIs of eligible patients were re-evaluated for the study. Suspicious regions of interest (ROIs) were evaluated by a radiologist with 4 years of experience in uroradiology and scored based on Prostate Imaging Reporting and Data System (PIRADS) v2.1. The reader was blinded to the pathological outcomes of any biopsy specimen. Lesions with a PIRADS score ≥3 were considered positive and included in the study. All cases were evaluated histopathologically by a pathologist with ten years of experience in uropathology. We utilized the mapping method which provided exactly the same information as the whole-mount histopathology along with processing the entire prostatectomy specimen. Results. A total of 142 histopathologic tumoral lesions were detected among 70 patients. In relation to postoperative histopathology, tumor multifocality was established in 78.6% (n = 55), and 52.1% (n = 74) of 142 foci recognized were clinically significant. By detecting a total of 67 lesions, mpMRI showed an overall sensitivity of 47%. Whilst the sensitivity was 73% (54/74) in clinically significant lesions, the sensitivity was only 17.6% (12/68) in clinically insignificant lesions. For the group with detected tumors, the mean prostate-specific antigen (PSA) and PSA density were higher, there were more high-grade lesions, and the rate of the extraprostatic extension was significantly greater (p<0.05, respectively). According to the multivariate analysis, only tumor size and Gleason Score (GS) were independent predictors regarding the ability of mpMRI to detect tumor foci within the prostate (p<0.0001). Conclusion. mpMRI exhibited an acceptable sensitivity in detecting high-risk and large Pca foci. The diagnostic accuracy is observed to be markedly diminished in small, low GS, and nonindex tumors. A considerable percentage of missed lesions are clinically significant.